2006
DOI: 10.1164/rccm.200508-1196oc
|View full text |Cite
|
Sign up to set email alerts
|

Partial Liquid Ventilation in Adult Patients with Acute Respiratory Distress Syndrome

Abstract: PLV at both high and low doses did not improve outcome in ARDS compared with CMV and cannot be recommended for patients with ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 39 publications
3
89
1
2
Order By: Relevance
“…On the other hand, because the study was focused on the efficacy of aerosolized PFC, the control group was composed of untreated animals, which significantly differs from a clinical setting, where the subjects would almost certainly be spontaneously breathing. Future studies should elucidate whether aerosolized PFC is superior to PLV in preterm lambs, as previously found in a pediatric porcine model with surfactant depletion (1), and whether this therapeutic approach can avoid the "peridosing" adverse effects associated with PLV (11,30). The potential additive effect of aerosolized PFC to surfactant therapy should be explored as well, as it has been demonstrated for PLV (31).…”
Section: Aerosolized Pfc In Experimental Rdsmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, because the study was focused on the efficacy of aerosolized PFC, the control group was composed of untreated animals, which significantly differs from a clinical setting, where the subjects would almost certainly be spontaneously breathing. Future studies should elucidate whether aerosolized PFC is superior to PLV in preterm lambs, as previously found in a pediatric porcine model with surfactant depletion (1), and whether this therapeutic approach can avoid the "peridosing" adverse effects associated with PLV (11,30). The potential additive effect of aerosolized PFC to surfactant therapy should be explored as well, as it has been demonstrated for PLV (31).…”
Section: Aerosolized Pfc In Experimental Rdsmentioning
confidence: 87%
“…The benefits of intratracheally instilled PFC for respiratory support are well known (2-10). However, clinical trials have failed to demonstrate the superiority of PLV over standard care (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perfluorochemical (PFC) liquids are inert, nontoxic liquids that had been extensively investigated for use in preclinical models of lung injury and in clinical application of partial liquid ventilation (PLV) for diseased lungs (Leach et al, 1996;Hirschl et al, 2002;Kacmarek et al, 2006). Although liquid ventilation has generally fallen from clinical use, administration of perflubron (LiquiVent; Alliance Pharmaceutical, San Diego, CA) and other PFC liquids in PLV was safe and could improve oxygenation and lung mechanics while also decreasing histopathological injury and inflammation in injured lungs (Hirschl et al, 1995(Hirschl et al, , 2002Leach et al, 1996;Rotta et al, 1999;Kacmarek et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although liquid ventilation has generally fallen from clinical use, administration of perflubron (LiquiVent; Alliance Pharmaceutical, San Diego, CA) and other PFC liquids in PLV was safe and could improve oxygenation and lung mechanics while also decreasing histopathological injury and inflammation in injured lungs (Hirschl et al, 1995(Hirschl et al, , 2002Leach et al, 1996;Rotta et al, 1999;Kacmarek et al, 2006). More recently it has been found that inhalation of nebulized perflubron and other PFC compounds comparably enhances oxygenation and improves lung mechanics in preclinical models of lung injury (Bleyl et al, 1999;Kandler et al, 2001Kandler et al, , 2004Ragaller et al, 2001;von der Hardt et al, 2004;Gama de Abreu et al, 2005;Meinhardt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%